2023
DOI: 10.3390/md21070420
|View full text |Cite
|
Sign up to set email alerts
|

Marine Microbial Polysaccharides: An Untapped Resource for Biotechnological Applications

Abstract: As the largest habitat on Earth, the marine environment harbors various microorganisms of biotechnological potential. Indeed, microbial compounds, especially polysaccharides from marine species, have been attracting much attention for their applications within the medical, pharmaceutical, food, and other industries, with such interest largely stemming from the extensive structural and functional diversity displayed by these natural polymers. At the same time, the extreme conditions within the aquatic ecosystem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 135 publications
0
2
0
Order By: Relevance
“…It has been shown that the Clavispora lusitaniae produces extracellular polysaccharides during metabolism. These polysaccharides have a variety of physiological and pharmacological activities, such as anti-tumor, anti-aging and anti-infection [41]. The advantage of using microbial fermentation to prepare fermentation broth for direct applications in food and cosmetics is that no organic reagents are required in the fermentation process that may produce substances in their metabolism that are beneficial to the fermentation substrate in terms of its efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the Clavispora lusitaniae produces extracellular polysaccharides during metabolism. These polysaccharides have a variety of physiological and pharmacological activities, such as anti-tumor, anti-aging and anti-infection [41]. The advantage of using microbial fermentation to prepare fermentation broth for direct applications in food and cosmetics is that no organic reagents are required in the fermentation process that may produce substances in their metabolism that are beneficial to the fermentation substrate in terms of its efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their features viz. antimicrobial, antioxidant, good flavor, gelling agent, drug carrier, surfactant, flocculating, emulsification etc., EPSs are utilized in a wide range of industries including food, paint, textile, medicine, pharmaceutical, and agriculture [2,3]. Microbial EPSs have widespread applicability and commercial value viz.…”
Section: Introductionmentioning
confidence: 99%